Cancer-Related Insomnia. (November 2014) - Induru, Raghava R; Walsh, Declan
Insomnia increases cancer symptom burden and impairs quality of life. The lack of standard definitions and treatment guidelines makes management difficult. Insomnia is common in most cancers but appears particularly so in lung, breast, and head and neck tumors. Older women seem most susceptible. Insomnia not only affects patients with cancer but also caregivers and families. Systematic screening is important. Few validated assessment scales are available. Nonpharmacologic therapies like cognitive behavioral therapy may help. New nonbenzodiazepine hypnotics may have some therapeutic advantages over older agents. Management of associated or contributory symptoms like fatigue, pain, and hot flashes with appropriate symptom-specific agents is important. Successful management may have a significant positive impact on global quality of life.